Deforestation Impacts on Diversity of Orchids with Inference on the Conservation Initiatives: Malaysia Case Study - Edward Entalai Besi; Muskhazli Mustafa; Christina Seok Yien Yong; Rusea Go (The Botanical Review, 2023)
Monitoring the impact of anthropogenic and naturogenic threats on orchid community through diversity, taxonomy and conservation studies is necessary. Reintroduction of these species to their natural habitat associates with their resilience, selection of suitable trees and sites for regeneration and restoration efforts, drives the conservation initiative. Upon obtaining an accurate estimate of the diversity for genetic resource conservation, integrative methods of classical morphological taxonomy, anatomy (micromorphology), and molecular genetics are crucial to solve the taxonomic uncertainty. Changes in microclimatic conditions and habitat structures are the key determinants of both epiphytic and terrestrial orchids assemblages following disturbance. Any assessments of biodiversity and ecosystem service must include variable forest types and management regimes to provide impartial views on the effect of forest and ecological disturbance on the orchid community. Accordingly, a plant-microbial ecology study should be included to study the extent of human-induced climatic variability towards the orchid diversification.